BIOACCUMULATION OF ORGANOCHLORINES PESTICIDES (OCP) COMPOUND IN GREEN MUSSELLS (Perna viridis) IN JAKARTA BAY - . Edward (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
ABSTRACTThe green mussel, Perna viridis can be used to determine bioaccumulation levels of organochlorine pesticides in a marine environment. Measurements on pesticide organochlorine concentration in green mussels (Perna viridis) were conducted in March and  May 2013. The purpose of this research was to determine the bioaccumulation level of organochlorine pesticides in green mussels which were  cultivated in Jakarta Bay. The samples were collected in Jakarta Bay in March and May 2013. The organochlorine pesticides concentration were measured  by gas chromatography HP 5890 series II. The results showed that the average concentration of organochlorine pesticides in the small size of green mussells was 12.842 ppb, in the medium size was 27.065 ppb, and in the big size was 108.646 ppb. These concentrations were still lower than safety threshold limit value for seafood stated by EPA (Environment Protection Agency) i.e., 1,500 ppb. The comparation between organochlorine pesticide concentration in seawater and organochlorine pesticide in green mussels (bioaccumulation factor) were 2,140 for small green mussel, 4,510 for medium green mussel, and 18,107 for big green mussels, respectively.Keywords: bioaccumulation, green musselss, organochlorine pesticide, Jakarta Bay